Quantitative PCR analysis of genes expressed during biofilm development of methicillin resistant Staphylococcus aureus (MRSA) - Atshan, Salman Sahab; Shamsudin, Mariana Nor; Karunanidhi, Arunkumar; Belkum, Alex van; Lung, Leslie Than Thian; Sekawi, Zamberi; Nathan, Jayakayatri Jeevajothi; Ling, King Hwa; Seng, Johnson Shueh Chong; Alreshidi, Mateq Ali; Abduljaleel, Salwa A.; Awang Hamat, Rukman (Elsevier, 2013)
Staphylococcus aureus biofilm associated infections remains a major clinical concern in patients with indwelling devices. Quantitative real-time PCR (qPCR) can be used to investigate the pathogenic role of such biofilms. We describe qPCRs for 12 adhesion and biofilm-related genes of four S. aureus isolates which were applied during in vitro biofilm development. An endogenous control (16S rRNA) was used for signal normalization. We compared the qPCR results with structural analysis using scanning electron microscopy (SEM). The SEM studies showed different cellular products surrounding the aggregated cells at different times of biofilm formation. Using qPCR, we found that expression levels of the gene encoding fibronectin binding protein A and B and clumping factor B (fnbA/B and clfB), which involves in primary adherence of S. aureus, were significantly increased at 24h and decreased slightly and variably at 48 h when all 4 isolates were considered. The elastin binding protein (ebps) RNA expression level was significantly enhanced more than 6-fold at 24 and 48 h compared to 12h. Similar results were obtained for the intercellular adhesion biofilm required genes type C (icaC). In addition, qPCR revealed a fluctuation in expression levels at different time points of biofilm growth of other genes, indicating that different parameter modes of growth processes are operating at different times.